Strategic Innovation in Tourism: A SWOT-Based Approach to Boost Service Utilization - Febrianti, Felisha; Nugroho, Dian Ari (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
Purpose – This study aims to identify effective business strategies for increasing tourists’ intention to use the services of PT Malang VW Tour, a tourism service provider offering classic Volkswagen tour experiences in Malang City. Design/Methodology/Approach – This study employs a descriptive qualitative approach by analyzing internal and external business conditions. Primary and secondary data were collected through observations, interviews, and questionnaires. The data were analyzed using strategic management tools, including SWOT analysis, Internal Factor Evaluation (IFE) matrix, External Factor Evaluation (EFE) matrix, and Internal-External (IE) matrix, to formulate appropriate business strategies. Findings – The results indicate that PT Malang VW Tour has strong potential to compete in the local tourism industry by offering unique and authentic travel experiences. Based on the SWOT analysis, the recommended strategies include developing tourism packages through strategic partnerships and expanding the vehicle fleet to improve service quality and innovation. The implementation of these strategies is expected to strengthen market competitiveness, increase tourist interest, and support sustainable business growth. Originality/Value This research is original in applying integrated SWOT, IFE, EFE, and IE analyses to a vintage tourism service context. The findings provide practical value by offering strategic recommendations to enhance service quality, partnerships, and business sustainability.